Impact of Treatment Delay and Prognostic Factors in Acute Myelitis of Neuromyelitis Optica Spectrum Disease - Luyao Zhou; Ziyu Liao; Yingming Long; Zhibin Li; Wei Qiu; Zefeng Tan; Tingting Lu (Brain and Behavior)
ABSTRACT Objective This study aims to investigate the relationship between treatment delay and poor prognosis in acute myelitis of Neuromyelitis Optica Spectrum Disorder (NMOSD). Additionally, we seek to explore the related factors that contribute to poor prognosis, with the intention of providing more precise clinical guidance. Methods We retrospectively analyzed the acute myelitis attacks of NMOSD patients who were continuously followed up or referred to our hospital from January 2018 to September 2022. We further calculated the proportion of clinical score improvement: (acute‐follow‐up)/(acute‐baseline); poor prognosis was assigned to 0%–33% improvement. The relationship between treatment delay and poor prognosis was evaluated with clustered Receiver Operating Characteristic (ROC) analysis. A Generalized linear mixed model was used to analyze the related factors. Results This study included a total of 144 episodes of myelitis attacks, of which 21.5% (31/144) resulted in poor prognosis. Based on the results of the clustered ROC analysis, it has been determined that treatment delay holds significant predictive value for poor prognosis (p = 0.001), with the optimal cut‐off point being 15 days. The generalized linear mixed model revealed that factors contributing to poor prognosis in NMOSD myelitis include age (OR, 1.041; CI, 1.013–1.071; p = 0.004) and treatment delay (OR, 1.034; CI, 1.014–1.054; p = 0.001). Conclusion Our results confirm the treatment delay and age as predictors of poor prognosis in acute myelitis of NMOSD.